Rayleigh-Bénard convection of a gas-vapor mixture with abnormal dependence of thermal expansion coefficient on temperature. (May 2021) - Zhang, Li; Hu, Yu-Peng; Yu, Jia-Jia; Li, You-Rong
Abstract: In order to reveal basic characteristics of Rayleigh-Bénard convection (RBC) of a gas mixture, which has abnormal dependence of thermal expansion coefficient on temperature, we presented a direct numerical simulation on RBC of a gas mixture of oxygen and cyclohexane near its maximum density. The influences of the density inversion parameter and the Rayleigh ( Ra ) number on the critical conditions of the flow onset and destabilization were analyzed. The flow evolution with Ra was exhibited. The results show the critical value of Rayleigh number of the flow onset is approximately proportional to the fourth power of the thickness of the upper stable sublayer. Regardless of density inversion parameter, the flow pattern at the flow appearance always has a multicellular structure. With increasing Ra, the multicellular flow structure would be transformed into various steady flow patterns, including parallel flow and pendant pattern. When the density inversion parameter is small, the unsteady flow cells exhibit a back and forth motion along the border. However, at a large density inversion parameter, the cells swing around the centers of the flow rolls. We also found that the local Nusselt ( Nu ) number on the bottom depends on the flow pattern. The average Nu increases gradually with increasing Ra under a small density inversion parameter. However, an abrupt rise of the average Nu appeared under a large density inversion parameter.